2020
DOI: 10.5530/ijpi.2020.3.46
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured Lipid Carriers (NLC): A Targeting Approach to the Brain via Intranasal Administration

Abstract: Different barriers like a blood-brain barrier in the brain restrict the transport of potential therapeutic elements for direct entry into the brain. For delivery of a wide range of therapeutic drugs directly to the brain can be achieved by direct targeting the brain via an olfactory and trigeminal neural pathway which bypasses the blood-brain barrier hence has gained more importance and considered as an accurate route of drug targeting to brain. Intranasal route transports the drug by delivering it directly to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Anatomically, the trigeminal pathway was abundant in the intradermal facial area and had numerous blood vessels directly connecting the face to the brain. 16 Previous research showed that intradermal facial injections are delivered more efficiently than the IN route. 17 However, these injections caused pain and were challenging to administer without professional assistance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anatomically, the trigeminal pathway was abundant in the intradermal facial area and had numerous blood vessels directly connecting the face to the brain. 16 Previous research showed that intradermal facial injections are delivered more efficiently than the IN route. 17 However, these injections caused pain and were challenging to administer without professional assistance.…”
Section: Introductionmentioning
confidence: 99%
“…However, this route of administration was challenged by the mucociliary clearance mechanism, which rapidly eliminated the drug before reached the respiratory tract, resulting in reduced therapeutic efficacy of TMN. , Nasal-to-brain delivery through the trigeminal pathway in the face could be a solution for delivering the TMN-NC system to the brain. Anatomically, the trigeminal pathway was abundant in the intradermal facial area and had numerous blood vessels directly connecting the face to the brain . Previous research showed that intradermal facial injections are delivered more efficiently than the IN route .…”
Section: Introductionmentioning
confidence: 99%